Sequential Steps of Chromosomal Differentiation in Atlantic Surgeonfishes: Evolutionary Inferences - Paulo Roberto Antunes de Mello Affonso; Maria Aparecida Fernandes; Josivanda Santos Almeida; Wagner Franco Molina (The Scientific World Journal)
Surgeonfishes are a species-rich group and a major biomass on coral reefs. Three species are commonly found throughout South Atlantic, Acanthurus bahianus, A. chirurgus, and A. coeruleus. In this paper, we present the first cytogenetic data of these species, revealing a sequential chromosomal diversification. A. coeruleus was characterized by a relatively conserved karyotype evolved by pericentric inversions of some pairs (2n=48, 2sm + 4st + 42a). In contrast, the karyotypes of A. bahianus (2n=36) and A. chirurgus (2n=34) were highly differentiated by the presence of six large metacentric pairs in A. bahianus (12m + 2sm + 4st + 18a) and A. chirurgus (12m + 2sm + 4st +1 6a) probably derived by chromosomal fusions that corroborate their closer relationship. A discernible in tandem fusion represents an autapomorphic character to A. chirurgus. In spite of macrostructure variation, single nucleolar organizer regions (NORs) on short arms of a subtelocentric pair and similar distribution of C-bands were observed in the three species. Overlapping of chromosomal data with molecular phylogeny indicated pericentric inversions which took place nearly at 19 Ma while centric fusions are as recent as 5 Ma. A physical mapping of coding and noncoding sequences in Acanthurus could clarify the role of additional rearrangements during their chromosomal evolution.